Apparent diffusion coefficient metrics for adult-type diffuse gliomas classified according to WHO 2021: a systematic review - Dragos Gabriel Margalin; Razvan Stanciulescu; Didina-Catalina Barbalata; Corneliu Toader (Egyptian Journal of Radiology and Nuclear Medicine, 2026)
Abstract Purpose This study aimed to determine the associations of apparent diffusion coefficient (ADC) values with the molecular and histological subtypes of adult-type diffuse gliomas classified in accordance with the 2021 World Health Organization (WHO) Classification of Tumors of the Central Nervous System, fifth edition (WHO CNS5). Methods PubMed, Scopus, Cochrane and Google Scholar were searched to identify relevant studies up to December 2025. The search and selection strategies followed the relevant items of the PRISMA 2020 statement. Open-access studies, written in English, that targeted the imaging characterization of adult-type diffuse gliomas classified based on WHO CNS5 and presented quantitative ADC data were included. Studies targeting pediatric gliomas, adult gliomas classified after prior editions of the WHO Classification of Tumors of the Central Nervous System or not presenting numerical ADC values were excluded. Due to high heterogeneity in imaging methodologies, ADC acquisition, ADC quantification and diagnostic targets, meta-analysis was not considered methodologically appropriate. Instead, quantitative data are further presented through a structured narrative synthesis. The quality of the selected studies was analyzed using the Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) tool. This review was not registered and received no funding. Results Fifteen eligible studies were selected, including a total of 1706 glioma patients. The reported ADC metrics and imaging protocols presented significant variability across studies. IDH-wildtype gliomas exhibited the lowest ADC values (0.78–1.48 × 10⁻ 3 mm 2 /s). An inverse correlation between the histological grade and ADC values was observed. The mean ADC sensitivity for IDH status ranged from 65.4% to 85.9%, with a broader range in diagnostic specificity (35–91.4%). Conclusion ADC may serve as an accessible imaging biomarker for the noninvasive characterization and differential diagnosis of WHO CNS5-classified adult-type diffuse gliomas. However, its stand-alone diagnostic utility remains limited due to the heterogeneity in acquisition, measurement and reporting methods, which show overlapping of ADC values between tumor subtypes and variable diagnostic performance. Furthermore, variability in reporting and methodology limits the standardization of diagnostic thresholds.